Pendampingan Penyusunan Evaluasi Kurikulum Merdeka Bagi Guru Kelas di Kepanewon Semin: Pengabdian - Paradika Angganing; Moefty Mahendra; Pujiyana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to improve teachers' knowledge and skills in designing and making learning evaluations based on the Merdeka Curriculum. The number of participants was 30 teachers spread across Kepanewon Semin. The training method used is introduction, practice, and implementation. The results of the service that has been carried out are that teachers' skills have improved in designing and making evaluations, both formative and summative assessments. Teachers' skills improved in terms of modifying assessments according to student needs.